A Pragmatic Analysis of Maxim Flouting Committed by The Characters in Avengers: Infinity War Movie - Jihan Nurjannah; Bukhari Daud; Ika Apriani Fata (Universitas Syiah Kuala, 2020)
This research is a pragmatic study which aims to find out the maxim flouting committed by the characters in Avengers: Infinity War movie and to describe its maxim flouting strategies. This research was conducted by using qualitative method. The data were collected by watching the movie and reading its transcript. Then they were analysed and classified based on the type of maxim flouting by Grice’s (1975) Cooperative Principles theory and Cutting (2002) Grundy’s (2000) modified theories of maxim flouting strategies. The results of this research show that the characters in the movie committed to flout all four types of Gricean maxims, which includes quantity, quality, relevance, and manner. Based on the occurrence frequency, flouting maxim of quantity was the most-flouted, while flouting maxim of manner was the least. Meanwhile, they also used all ten kinds of strategies to flout the maxims, including, overstatement, understatement, metaphor, irony, banter, sarcasm, irrelevant statement, ambiguous statement, tautology, and rhetorical question. In this movie, the characters tend to use overstatement very frequently among other strategies which makes it the highest use percentage.